PROGRESS IN THE REALIZATION OF THE PROJECT FON-DUSHANBE CATALOGUE - Mullo-Abdolov, A.; Relke, H.; Kokhirova, G.; Yuldoshev, Q.; Protsyuk, Yu.; Andruk, V. (Одеські астрономічні публікації, 2018)
Since May 2018 the process of the scanning and processing of photographic plates from the archive of the Institute of Astrophysics Academy of Sciences of Tajikistan has begun. It is a matter of approximately 1560 photographic plates in the sky zones from -8 to +90 degrees that were exposed for the FON project in the Hissar observatory (HisAO) during 1985-1992. The plates are digitized by using of the scanner Microtek ScanMaker 1000XL Plus with the resolution of 1200 dpi. The size of the photographic plates is 8°x8° or 30x30 cm, the size of the digitized images is 13000 x 13000 px. So far the first results of the processing of the 71 plates of zero zone and the 58 plates of 64, 68 and 72 zones were obtained. The errors in the definition of equatorial coordinates and B- magnitudes for the stars in the range of 5m - 17m are the following: σαδ = ±0.33" and σB = ±0.12m. The differences between the calculated positions and B-magnitudes and the reference one from the Tycho2 catalogue are σαδ = ±0.12" and σBT = ±0.19m respectively. The difference between the calculated and the photoelectric B-magnitudes equals σB = ±0.15m. In the realization of the “FON- Dushanbe catalogue” project five astronomical institutions are involved: Institute of Astrophysics of AS of Republic of Tajikistan; Walter Hohmann Observatory, Essen, Germany; Ulugh Beg Astronomical Institute UAS, Uzbekistan; Research Institute “Mykolaiv Astronomical Observatory”, Ukraine and Main Astronomical Observatory NASU, Ukraine.